Exploring Intermediality in Art History and its Application in the Educational Sector - Themis Veleni (Syn-Thèses, 2024)
Intermediality is one of the most intriguing and discussed concepts within the contemporary art world, with a rich history in aesthetics. As a modern and contemporary artistic practice has disrupted conventional boundaries and pushed the limits of perception, leading to the emergence of innovative art forms and genres and challenging our understanding of the meaning of art.  Intermediality is closely intertwined with multisensoriality, enabling artists to explore the use of different media, such as sound, light, and movement, in their works, leading to a truly multimodal experience for viewers. It has the potential to transform the way we educate ourselves about various subjects, including art, in a more comprehensive and immersive manner by engaging all our senses. In this article, I aim to explore the idea of intermediality from two different angles, by analyzing and classifying certain modern and contemporary artworks into different intermediality categories, and by discussing how intermediality relates to education, particularly within the context of the Master of Art Education program at the University of Granada. The postgraduate students of this course are provided with a methodology that helps them develop innovative learning activities centered around the idea of intermediality.